2021
DOI: 10.1002/dneu.22839
|View full text |Cite
|
Sign up to set email alerts
|

Aging affects cognition and hippocampal ultrastructure in male Wistar rats

Abstract: It is now well established that aging is associated with emotional and cognitive changes. Although the basis of such changes is not fully understood, ultrastructural alterations in key brain areas are likely contributing factors. Recently, we reported that aging‐related anxiety in male Wistar rats is associated with ultrastructural changes in the central nucleus of amygdala, an area that plays important role in emotional regulation. In this study, we evaluated the cognitive performance of adolescent, adult, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…In presynaptic boutons, aging elicits region-divergent adjustments of mitochondrial contents. Ultrastructural analysis of the hippocampal CA1 area prepared from male rats found significantly reduced numbers of mitochondria per presynaptic bouton, accompanied by an increased individual mitochondrion area in aged rats compared to adolescent and adult rats [ 331 ]. These synaptic mitochondria in aged synapses also exhibit functional impairment, including decreased Ca 2+ buffering capacity, reduced ATP production, and increased oxidative stress [ 332 334 ].…”
Section: Introductionmentioning
confidence: 99%
“…In presynaptic boutons, aging elicits region-divergent adjustments of mitochondrial contents. Ultrastructural analysis of the hippocampal CA1 area prepared from male rats found significantly reduced numbers of mitochondria per presynaptic bouton, accompanied by an increased individual mitochondrion area in aged rats compared to adolescent and adult rats [ 331 ]. These synaptic mitochondria in aged synapses also exhibit functional impairment, including decreased Ca 2+ buffering capacity, reduced ATP production, and increased oxidative stress [ 332 334 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies showed that, compared with young rats, the expression of P16 protein and senescence-associated β-galactosidase (sa-β-gal) in the hippocampus of aging rats were increased [17]. Other investigations have shown that the learning and memory ability of aging rats was decreased in the natural aging rat model compared with young rats [18][19][20]. In this study, we investigated the mRNA and lncRNA expression profiles in the hippocampal tissue of aging rats and constructed a lncRNA-miRNA-mRNA competing endogenous RNA (ceRNA) network by adopting RNA sequencing technology to offer a new theoretical foundation for targeted remedies for aging.…”
Section: Introductionmentioning
confidence: 99%